Membangun model konseptual faktor sinergitas perilaku konsumen dalam konteks pembelian impulsive secara online - Harries Arizonia Ismail; Emi . Trimiati; Yani . Prihati (University of Darussalam Gontor, 2020)
The development of this conceptual model is directed to encourage consumer purchases of products where this process occurs by online. The research model developed is called a synergy factor which includes system factors, internal factors, external factors and product factors. Each of these factors has characteristics in the form of variables consisting of website aesthetics from system factors, availability of money from internal factors, word of mouth from external factors and price perception of product factors. These four elements will determine the interest that will ultimately drive the purchase. The process in this research model is not in purchases that generally occur but in impulsive purchases or purchases without planning.